Healthy Spinach Noodles: A Functional Food Innovation for Children Who are Reluctant to Eat Vegetables - Najah, Salwa Maziatun; Hidayati, Irul; Tyastirin, Esti (International Conference on Sustainable Health Promotion, 2025)
Vegetable consumption among children in Indonesia is still very low, while instant noodle consumption is very high. This raises concerns about long-term health impacts. A food innovation is needed that can insert vegetable intake into foods that are already popular with children, such as noodles. This study aims to create and test consumer acceptance of a functional food innovation in the form of healthy spinach noodles as an alternative strategy to increase vegetable consumption. This study is an experimental study with organoleptic testing of 34 respondents. Data were collected through a questionnaire with a hedonic scale of 1-5. The results of the organoleptic test showed a very high overall acceptance level of 83.2%. In detail, the appearance aspect achieved acceptance of 97%, taste 91%, texture 79%, color 85%, and aroma 64%. No respondents gave a rating of dislike or somewhat dislike in all aspects. The healthy spinach noodle innovation was successfully created and very well received by respondents in terms of organoleptic. This product has great potential to be an effective strategy to increase vegetable intake, especially in children who are reluctant to consume vegetables in their whole form.